STRATEGI PENANGGULANGAN STUNTING OLEH DINAS KESEHATAN KABUPATEN ROKAN HULU - Mardiana Evita Sari; Mimin Sundari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Stunting Prevention Strategy by the Rokan Hulu District Health Office on the background of the failure to thrive in children under five due to lack of coronary nutrition, especially in the first 1,000 days of life (HPK). Therefore, it is necessary to have a stunting control strategy, this study was conducted to analyze the stunting prevention strategy by the Rokan Hulu District Health Office and to find out the inhibiting factors, the theory used was the theory of strategy implementation by Wheelen and Hunger in (Ryanto) which has three indicators such as program development, The budget and procedures for this type of research are qualitative with a case study approach. This research was conducted at the Rokan Hulu District Health Office. With the types and sources of premier data and secondary data with observation, interview, documentation and data collection techniques, based on the research that has been done, it can be concluded that the stunting prevention strategy by the Rokan Hulu District Health Office is running well because it is approaching the achievement rate of reducing stunting. However, in the implementation of the strategy, there were inhibiting factors that were found, such as: the economic condition of the community, differences in perceptions, newcomers, and the level of community knowledge. Keywords: Strategy, Stunting Prevention